A Novel Spider Toxin Inhibits Fast Inactivation of the Nav1.9 Channel by Binding to Domain III and Domain IV Voltage Sensors - Peng, Shuijiao; Chen, Minzhi; Xiao, Zhen; Xiao, Xin; Luo, Sen; Liang, Songping; Zhou, Xi; Liu, Zhonghua (Frontiers in Pharmacology, 2021)
Venomous animals have evolved to produce peptide toxins that modulate the activity of voltage-gated sodium (Nav) channels. These specific modulators are powerful probes for investigating the structural and functional features of Navs. Here, we report the isolation and characterization of δ-theraphotoxin-Gr4b (Gr4b), a novel peptide toxin from the venom of the spider Grammostola rosea. Gr4b contains 37-amino acid residues with 6 cysteines forming 3 disulfide bonds. Patch-clamp analysis confirmed that Gr4b markedly slows the fast inactivation of Nav1.9 and inhibits the currents of Nav1.4 and Nav1.7, but does not affect Nav1.8. It was also found that Gr4b significantly shifts the steady-state activation and inactivation curves of Nav1.9 to the depolarization direction and increases the window current, which is consistent with the change in the ramp current. Furthermore, analysis of Nav1.9/Nav1.8 chimeric channels revealed that Gr4b preferentially binds to the voltage-sensor of domain III (DIII VSD) and has additional interactions with the DIV VSD. The alanine-screening analysis indicated that N1139 and L1143 in DIII S3-S4 linker participate in toxin binding. In sum, this study reports a novel spider peptide toxin that may slow the fast inactivation of Nav1.9 by binding to the new neurotoxin receptor site-DIII VSD. Taken together, these findings provide insight into the functional role of the Nav channel DIII VSD in fast inactivation and activation.